HYDROPHYSIO-CHEMICAL EXAMINATION OF WASTES WATER COLLECTED FROM EFFURUN ABATTOIR - Ugbune, Ufuoma; Aregbor, Okagbare (FUDMA Journal of Sciences, 2024)
The purpose of this study is to examine the physiochemical qualities of abattoir wastewater. Weekly sampling of abattoir waste was done for four weeks. Standard laboratory procedures were followed in the analysis of sample wastewater, this is to ensure standard results. In this study, the pH of abattoir wastewater is in the range of alkaline region and also falls within the permissible levels of World Health Organization (WHO) for discharging wastewater. The dissolved oxygen (DO) is below the allowable limit of water while that of biochemical oxygen demand (BOD) is above the allowable limit set by WHO. The concentration of total nitrogen and phosphate in sample wastewater is above the standard limit set by WHO. The value of magnesium is quite higher when compared with the standard recommended by WHO. Therefore, the release of abattoir waste into the receiving water could lead to surface water pollution. The result of heavy metals in this research is below the permissible level of WHO, however the receiving water needs regular monitoring. Arising from the results obtained from this research, abattoir wastewater needs treatment before discharge into receiving water. It is also important for agencies of government to monitor surface water receiving abattoir effluents regularly.
Keywords: Wastewater; Abattoir; Dissolve oxygen; Biochemical oxygen demand